(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The biologically active substances contained in the dry extract of walnut shells were studied. This extract was obtained from various raw materials, and the results of comparative analysis of arabinose and galactose in its content were presented.